Analysis of the Effect of an Installation of a Single Tuned Passive Filter on Harmonics and Distribution Transformers - Zulfatri Aini; Zainal Ahnur; David Setiawan; Ahmad Fudholi (Institute of Advanced Engineering and Science, 2018)
Non-linear loads on power systems cause harmonics and losses in distribution transformers. Results of the measurements on the two distribution transformers showed several phase transformer test-driven development (TDD) values above the standard SPLN D5.004-1: 2012. The values were 5.58% in the phase transformer, T 1 and 5.48% and 6.10% in S and T phases of the second transformer, respectively. In the calculations, the transformer losses due to harmonic currents were 1.64 kW in the phase transformer T 1, and 1.64 kW and 1.82 kW in the S and T phases of transformer 2, respectively. Designing a single-tuned passive filter based on the characteristics of the current, voltage, power, and power factor in the phase transformer with a value above the TDD standard can reduce the harmonics and losses. A filter with different specifications in each filtered phase transformer was obtained. The filter reduced the TDD value on the phase transformer T 1 to 3.55% and to 3.88% and 3.43% on the on phase T and S phases of transformer 2. Moreover, it reduced the losses to 0.73 kW on phase transformer T 1, and 1.02 kW and 0.92 kW on the S and T phases of transformer 2.